“Doctor, I Want to Be Like This!”: Exploring Global Beauty Body Standards Through a Multicenter Survey - Damiano Tambasco, MD; Jordi Mir, MD; Alfredo Hoyos, MD; David Sieber, MD; Mauricio Viaro, MD; Jack Zamora, MD; Carlos Manfrim, MD; Edwin Zara, MD; Federica Tomaselli, MD; Christian Montes, MD; Miriam Isola, MD; Maria De Martino, MD; et al. (Plastic and Reconstructive Surgery, Global Open)
Background:. Plastic surgery aims to enhance patients’ positive features and improve perceived flaws without seeking complete transformation. The body is a living organism, not a sculptural object to be reshaped at will. Aesthetic standards are influenced by subjective factors, including technology and social media’s effect on self-perception and beauty ideals. Understanding body perception requires consideration of personal views, mirror reflections, and external perspectives. Methods:. We analyzed data from more than 4000 patients to obtain objective insights into contemporary aesthetic preferences. We examined the influence of globalization on beauty standards, the relationship between physical activity and desired body definitions, and regional preferences for specific body shapes. In addition, we assessed how patients’ aesthetic preferences are shaped more by the surgical centers they choose than by their nationality. Results:. Our findings indicate that globalization has diversified perceptions of beauty, highlighting personal and cultural differences. We noted a significant correlation between patients’ aesthetic preferences and the surgical center, reflecting the impact of medical tourism and social media on shaping beauty ideals. Conclusions:. As patient opportunities expand, the remote management of complex procedures necessitates skilled surgeons to ensure safe and effective care. Our experience provides valuable data on current patient preferences, essential for adapting practices in the evolving landscape of plastic surgery.